Code of ethics for Filipino social scientists (1990)
We, Filipino social scientists, in our unceasing endeavor to attain the highest level of professional knowledge and competence, and in our commitment to the norms of objectivity, rational skepticism and critical judgment, uphold the search for truth, wherever it may lead. We shall enhance the understanding of the nature and behavior of human beings of their multifaceted interrelationships. We shall defend the integrity of the intellectual inter price, responsibility for human life and love of country. We shall never allow self-serving values to interfere with our service to science, society and the nation.
Keywords: Social scientists -- Professional ethics